Hand Hygiene Education To Improve Healthy Living Behavior At Al-Mahdhuri Islamic Junior High School, West Pesisir Regency, Lampung - Rizka Putri; Diana Rahmatillah; Kashif Khan (Health & Medical Sciences, 2026)
Hand hygiene is an effective preventive measure for preventing the transmission of infectious diseases, but its practice among school students remains suboptimal. This study aimed to evaluate the effectiveness of hand hygiene education in improving knowledge and healthy living behaviors among students at SMP IT Al-Mahdhuri in Pesisir Barat Regency, Lampung. The study used a pre-experimental, one-group pretest–posttest design with 107 participants (35 seventh-grade students, 38 eighth-grade students, 34 ninth-grade students, and two teachers). The intervention included educational materials, demonstrations, and practice of the six steps of handwashing according to WHO guidelines. Measurements were conducted using questionnaires before and after the intervention. Data analysis was conducted using descriptive quantitative methods by comparing average pretest and posttest scores, supported by observations of changes in skills and behavior. The results showed an increase in knowledge across all grade levels: seventh-grade students from 56% to 88.8%, eighth-grade students from 61% to 91.6%, and ninth-grade students from 62.3% to 96.5%. Furthermore, there was an increase in students' practical skills and habituation of hygienic behavior. It was concluded that hand hygiene counseling was effective in increasing students' knowledge, skills, and clean and healthy living behavior, thus potentially supporting the prevention of infectious diseases in the school environment.